A Study on the Operation of Librarian Learning Communities and Competency Improvement - Noh, younghee; Jung, Youngmi (International Journal of Knowledge Content Development & Technology, 2024)
In this study, we collaborated with the National Library of Korea’s Library Education Institute to pilot the operation of a librarian learning community and aimed to measure its effectiveness based on the improvement of librarian competencies. A total of 28 participants attended four programs, and the research results are as follows: First, when analyzing competencies in terms of community capacity, attitude competency was the highest, followed by knowledge and skills competencies in that order. The correlation analysis among competencies showed that there were mutual correlations among the three competencies. Second, in the pre-post analysis of the three competencies and their sub-competencies, it was found that all competencies, including sub-competencies, improved. Based on the research results, it was confirmed that through the operation of the librarian learning community, the average competencies of librarians can be improved, which can directly impact the enhancement of the library’s service capabilities. Therefore, it is believed that there is a need to activate the operation of librarian learning communities and explore nationwide dissemination strategies for the operating model.